Economic development and the impacts of natural disasters - Toya, Hideki; Skidmore, Mark (Economics Letters, 2007)

The macroeconomic consequences of disasters - Noy, Ilan (Journal of Development Economics, 2009)
Natural disasters have a statistically observable adverse impact on the macro-economy in the short-run and costlier events lead to more pronounced slowdowns in production. Yet, interestingly, developing countries, and smaller economies, face much larger output declines following a disaster of similar relative magnitude than do developed countries or bigger economies. A close study of the determinants of these adverse macroeconomic output costs reveals several interesting patterns. Countries with a higher literacy rate, better institutions, higher per capita income, higher degree of openness to trade, and higher levels of government spending are better able to withstand the initial disaster shock and prevent further spillovers into the macro-economy. These all suggest an increased ability to mobilize resources for reconstruction. Financial conditions also seem to be of importance; countries with more foreign exchange reserves, and higher levels of domestic credit, but with less-open capital accounts appear more robust and better able to endure natural disasters, with less adverse spillover into domestic production.

Measuring the total economic value of restoring ecosystem services in an impaired river basin: results from a contingent valuation survey - Loomis, John; Kent, Paula; Strange, Liz; Fausch, Kurt; Covich, Alan (Ecological Economics, 2000)
Keywords: Ouvrage_Collectif_Numéro1

Race, class, and Hurricane Katrina: Social differences in human responses to disaster. - Elliott, James R.; Pais, Jeremy (Social Science Research, 2006)
Hurricane Katrina pounded the Gulf South at the end of August 2005, devastating lives and raising questions about how race and class influence human, as well as institutional, responses to disaster. This study uses survey data collected from over 1200 Hurricane Katrina survivors to examine these influences on a wide array of responses, ranging from evacuation timing and emotional support to housing and employment situations and plans to return to pre-storm communities. Results reveal strong racial and class differences, indicating that neither of these dimensions can be reduced to the other when seeking to understand responses by survivors themselves. This intersection renders low-income black home owners from New Orleans those most in need of targeted assistance as residents work to put themselves and the region back together.

Social Vulnerability to Environmental Hazards - Cutter, Susan L.; Boruff, Bryan; Shirley, W. Lynn (Social Science Quarterly, 2003)
County-level socioeconomic and demographic data were used to construct an index of social vulnerability to environmental hazards, called the Social Vulnerability Index (SoVI) for the United States based on 1990 data. Copyright (c) 2003 by the Southwestern Social Science Association.